Improvement in Student Data Analysis Skills after Out-of-Class Assignments - Kristen L.W. Walton (American Society for Microbiology, 2016)
The ability to understand and interpret data is a critical aspect of scientific thinking. However, although data analysis is often a focus in biology majors classes, many textbooks for allied health majors classes are primarily content-driven and do not include substantial amounts of experimental data in the form of graphs and figures. In a lower-division allied health majors microbiology class, students were exposed to data from primary journal articles as take-home assignments and their data analysis skills were assessed in a pre-/posttest format. Students were given 3 assignments that included data analysis questions. Assignments ranged from case studies that included a figure from a journal article to reading a short journal article and answering questions about multiple figures or tables. Data were represented as line or bar graphs, gel photographs, and flow charts. The pre- and posttest was designed incorporating the same types of figures to assess whether the assignments resulted in any improvement in data analysis skills. The mean class score showed a small but significant improvement from the pretest to the posttest across three semesters of testing. Scores on individual questions testing accurate conclusions and predictions improved the most. This supports the conclusion that a relatively small number of out-of-class assignments through the semester resulted in a significant improvement in data analysis abilities in this population of students.